CAMPUS-BASED ENTREPRENEURSHIP DEVELOPMENT MODEL - Kafrawi Kafrawi; Fahrina Yustiasari Liriwati; Muhammad Ilyas; Mulyadi Mulyadi; Abdul Syahid (Yayasan Literasi Kita Indonesia, 2023)
Higher education as a place that facilitates citizens to get teaching, education and training as well as motivating students to become intelligent generations who are independent, creative, innovative and able to create various job (business) opportunities. For this reason, it is imperative for every tertiary institution to immediately change the direction of its higher education policies, both those that are high Learning university and Research University as well as in nature Entrepreneurial University. In forming entrepreneurentrepreneur Such young success requires seriousness and seriousness from the tertiary institution carry out the mission entrepreneurial campus. The forms of entrepreneurship programs that have been initiated and implemented by various tertiary institutions, especially in Indonesia, should be used as an example in starting to focus on tertiary institutions in producing entrepreneurs who young success. In addition, this idea can be a reference for lecturers in conducting lectures with innovative learning models to develop students' entrepreneurial spirit.